Integration of Responsible Consumption and Production Values (SDGs) in Seventh Grade Social Studies Learning - Raja Fennythia Siregar; Nuriza Dora (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This research aims to analyze the integration of SDG 12 values in the seventh-grade social studies learning at MTsN Pematang Siantar and to examine the role of social studies teachers in instilling responsible consumption and production values. The research uses a descriptive qualitative approach involving 11 informants selected purposively, consisting of the head of the madrasa, three social studies teachers, and seven students. Data were collected thru observation, semi-structured interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña thru the stages of data condensation, data presentation, and conclusion drawing. The research results show that the values of SDG 12 have been integrated into social studies learning by linking economic activity materials with environmental issues, applying contextual learning, discussions, case studies, and fostering environmentally friendly behavior supported by the Pancasila Student Profile Strengthening and Rahmatan lil 'Alamin (P5RA) program and madrasah culture. Social Studies teachers play the role of educators, facilitators, motivators, and role models in shaping students' knowledge, attitudes, and behaviors to apply the principles of Reduce, Reuse, and Recycle (3R). This research produces a conceptual model that emphasizes that the synergy between learning materials, teaching strategies, the role of teachers, school culture, and P5RA are the main factors for the successful integration of SDG 12 in IPS learning based on Education for Sustainable Development (ESD).